Essentials of Autopsy Practice Reviews, Updates, and Advances - Rutty, Guy N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book covers topical subjects within the field of death investigation, where changes in practice have recently occurred. As the area of dating of wounds has changed since the subject was addressed in a previous volume, this subject is revisited for the first time. The remaining subjects covered in this volume embrace the multi-disciplinary approach required for death investigation, and address advances in the field of forensic radiology imaging, pathology, and toxicology. There is also a chapter on cardiopulmonary resuscitation which explains clinical processes and procedures that may occur to an individual immediately before death that may have a bearing on the subsequent autopsy findings. Essentials of Autopsy Practice: Reviews, Updates and Advances is an educational and practical resource aimed at trainees and consultants, generalists and specialists, and the new multi-disciplinary team alike.
The role of cross-sectional imaging in the investigation of childhood deaths -- Vertebral artery trauma -- Death in Crowds -- New Psychoactive Substances -- Horse related Injuries and Deaths -- Cardiopulmonary Resuscitation -- The dating of injury; the five step approach. A clinical method to enlighten forensic aspects.
Keywords: Medicine; Forensic medicine; Pathology; Medical laws and legislation; Medicine & Public Health; Pathology; Forensic medicine; Medical Law